Learning Interest as a Predictor of Mathematics Achievement among Indonesian Junior High School Students - Erlando Doni Sirait; Dwi Dani Apriyani; Vickry Ramdhan; Fajar Erlangga (Mandalika Mathematics and Educations Journal, 2026)
Programme for International Student Assessment (PISA) reported that many countries, including Indonesia, have not yet reached the expected levels of mathematics proficiency, highlighting the importance of examining internal factors such as students’ learning interest. This study aims to examine students’ learning interest and how it relates to and predicts their mathematics achievement. This quantitative correlational study involved 65 randomly selected seventh-grade students from SMPN 160 East Jakarta, Indonesia. Learning interest was measured using a validated 20-item questionnaire, and mathematics achievement was obtained from mid-semester test scores. Data were analyzed using descriptive statistics, Spearman’s correlation, and rank-based and multiple regression analyses in SPSS 27. The results showed that students generally had moderate levels of learning interest (M = 3.65) and mathematics achievement (M = 78.94). Learning interest was positively related to mathematics achievement (r = 0.64) and significantly predicted students’ mathematics performance (R² = 0.52), with persistence (p = 0.03) and attention (p = 0.04) being the strongest predictors. In conclusion, students’ persistence and attention are key factors in mathematics achievement, indicating that sustained focus and perseverance play a central role in improving mathematics performance.